Peran Orang Tua dalam Memberikan Pengetahuan tentang Fiqih Haid di Kalangan Remaja Putri - Louisa Anwar Hasibuan; Anis Soraya; Rahma Nur Aisyah; Mutiara Hamda; Nur Rosyidah; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The role of parents in providing knowledge about menstrual jurisprudence among young women is very important. Because adolescence is a transition period between childhood and adulthood, during this period children will experience many changes both physically and psychologically. one of the changes is menstruation or menstruation which every young woman experiences. The aim of this research is to determine the role of parents in providing knowledge about menstrual fiqh among young women and the aim of the role of parents in providing knowledge about menstrual fiqh among young women is to help them understand and manage their menstrual cycle in accordance with Islamic teachings. The type of research used is descriptive qualitative research using books, magazines, offline and online articles or the latest journals, all data found from reading sources is then expressed in qualitative descriptive form. The results of this research show that the role of parents in providing knowledge about menstrual jurisprudence among teenagers is very important, this is to ensure that young women feel comfortable, healthy and independent in managing their menstruation. And know the differences between women's blood that comes out of their genitals, namely, menstrual blood, istihadhah blood, and postpartum blood. Apart from that, providing knowledge about menstrual jurisprudence can also help young women understand their responsibilities and obligations as Muslim women.